Determinant of Selection of Offline Marketing Model of Agricultural Products in Banjar Agropolitan City - Sri Mulyati; Hasan Fahmi Kusnandar; Maman Sulaeman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The agricultural sector still plays an important role at both the national and regional levels, but that role tends to decrease in line with the increase in per capita income reflecting a process of structural transformation. This decrease is due to the interaction of various processes that work on the demand side, supply and activity shifts. This research aims to analyze the determinant of the selection of offline marketing models of agricultural products in the agropolitan city of Banjar West Java. This research is categorized as explanatory research which is a study that aims to explain the causal relationship between variables through hypothesis testing. The Inference Statitic method used in the analysis of this research data is the path of analysis. Based on the results of research shows that the most influential factor on offline marketing selection is affordability that there are still consumers who have not yet reached information technology, then is trust, booster promotion, doubt and Competition.